A project case on treatment of photovoltaic enterprise production wastewater - YANG Weiqiu; SHI Guangyu (Gongye shui chuli)
Based on the quality characteristics of production wastewater from photovoltaic enterprises and the principles of separate collection and treatment, fluorine-containing wastewater was pretreated by coagulation and sedimentation before combing with comprehensive wastewater. The electrocatalysis-coagulation sedimentation-TMF-UASB-AO combination process was used to treat the mixed wastewater. The operation results showed that this process had a high removal rate for pollutants in the comprehensive wastewater of photovoltaic enterprises. The final removal rates of F-, CODCr, BOD5, NH4+-N, TN, and SS reached 89.1%, 97.6%, 96.5%, 90.6%, 84.3%, and 85.3%, respectively. The effluent quality could meet the requirements of Table 2 in the Pollutant Discharge Standards for Battery Industry (GB 30484-2013) for indirect discharge of water pollutants in new enterprises. The total project investment was 7.97 million yuan, and the operating cost was 8.36 yuan/t. Through biogas recovery and magnetic levitation fan energy-saving technology, the annual economic benefit was 340 000 yuan, which provided reference for the design and operation of wastewater treatment in photovoltaic enterprises.